2017
DOI: 10.1038/srep40650
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Catalyst-free Oxidation of D-Glucose to D-Glucuronic acid induced by High-Frequency Ultrasound

Abstract: This systematic experimental investigation reveals that high-frequency ultrasound irradiation (550 kHz) induced oxidation of D-glucose to glucuronic acid in excellent yield without assistance of any (bio)catalyst. Oxidation is induced thanks to the in situ production of radical species in water. Experiments show that the dissolved gases play an important role in governing the nature of generated radical species and thus the selectivity for glucuronic acid. Importantly, this process yields glucuronic acid inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 25 publications
3
33
0
2
Order By: Relevance
“…And other literatures have shown that similar sign change can be achieved through the later two methods in an H‐abstraction of glucose by OH radical. In a recent study, the tiny positive barrier for this reaction using B3LYP/def2‐TZVP in the gas phase was reverted to negative after including the solvent effect and the enthalpy correction . The author also mentioned that if there is the presence of OH radical within the conversion of the aldehyde species, the barriers could be even lower.…”
Section: Resultsmentioning
confidence: 99%
“…And other literatures have shown that similar sign change can be achieved through the later two methods in an H‐abstraction of glucose by OH radical. In a recent study, the tiny positive barrier for this reaction using B3LYP/def2‐TZVP in the gas phase was reverted to negative after including the solvent effect and the enthalpy correction . The author also mentioned that if there is the presence of OH radical within the conversion of the aldehyde species, the barriers could be even lower.…”
Section: Resultsmentioning
confidence: 99%
“…Other technologies such as high frequency ultrasound, milling and electrochemistry are also the topic of intensive studies in France. One may cite, for instance, the electrocatalytic dehydrogenation of polyols, the glycosylation of carbohydrates assisted by ball‐milling or the catalyst free oxidation of carbohydrates by high frequency ultrasound . Although promising results were claimed, the energy consumption related to these technologies is currently the main cost driver.…”
Section: Figurementioning
confidence: 99%
“…O ácido glicurônico é considerado um produto químico muito valioso, utilizado na indústria química, alimentícia e farmacêutica. Outro produto obtido a partir da glicose é o ácido hialurônico, o qual é aplicado na formulação de cosméticos devido a sua propriedade antioxidante, na medicina encontra aplicações nos tratamentos de catarata e artrite, além de ser um precursor do ácido ascórbico ou vitamina C (Pan et al,2014;Amaniampong et al, 2017).…”
Section: Introductionunclassified